Self-disclosure (Keterbukaan Diri) dan Quarter-life Crisis (Krisis Seperempat Abad) Mahasiswa Psikologi - Afifah Ulva Zein; Yuliadi, Istar; Subandono, Jarot; Septiawan, Debree (Fakultas Kedokteran, Universitas Sebelas Maret, 2023)
Introduction: Quarter-life crisis is an individual who enters the period of emerging adulthood without stopping questioning the future, confused in dealing with problems, and reflecting a lot on the past to see whether his life up to now is in accordance with the life he dreamed of. This crisis is most intense in their twenties and often occurs in someone who is in the transition phase from education to the next career level, for example, a final year student. Therefore, it is necessary to find a way to reduce the negative impacts that arise, which is by knowing more about the situation that being experienced by self disclosure. This study aimed to determine whether there is a relationship between self-disclosure and quarter-life crisis in final year students. Methods:This research was observasional analytics with cross-sectional design. Subject in this research was psychology student at UNS in year 2018, amounted to 46 people who met the inclusion and exclusion criteria. Sampling was done by pusposive sampling technique. The level of self-disclosure was measured by filling out the Self-disclosure questionnaire, while the degree of quarter-life crisis was measured by the Quarter-life Crisis questionnaire. The data obtained were then analyzed by spearman rank correlation test. Results: This study showed a significant and negative relationship between the level of self-disclosure with quarter-life crisis (sig f=0,049) Conclusions: Based on the results of this study, there was a moderate relationship between the level of self-disclosure and quarter-life crisis on psychology students Universitas Sebelas Maret year 2018, where the higher level of self-disclosure, the lower level of quarter-life crisis.